Peran Literasi Al-Qur’an Dalam Pembentukan Pemikiran Kritis Peserta Didik Di SMA Negeri 1 Wanasaba - Jumaah Jumaah; Syamsul Arifin (Journal on Education, 2024)
This study is a case analysis with the primary goal of exploring how Quranic literacy influences the development of critical thinking skills in students attending SMA Negeri 1 Wanasaba. Quranic literacy entails comprehending the Quranic texts and integrating them into daily thought processes and behaviors. The primary objective of this investigation was to examine the impact of students' comprehension of the Quran on their critical thinking development within this educational institution. The research utilized a case study methodology, incorporating data collection through extensive interviews with students, classroom observations, and an examination of documents associated with Quranic instruction at the school. Following data collection, a qualitative approach was employed for analysis. The findings of the study suggest that Quranic literacy has a notable influence on shaping students' critical thinking abilities. Students who have a deep understanding of the Quran tend to have the ability to analyze, evaluate, and comprehend various issues more critically. They are also able to relate the values contained in the Quran to the context of their daily lives. This research has important implications in the context of education at SMA Negeri 1 Wanasaba and may also be relevant to other schools with similar approaches. Understanding the role of Quranic literacy in shaping critical thinking can help in the development of more holistic and sustainable educational programs and assist students in developing more analytical and critical thinking skills to face various challenges in their lives